Exploration on Cross-cultural Tolerance in Medical Care for Indigenous Tibetan Patients in Ultra-High-Altitude Areas - Feifei YU; Guangyong WANG; Jia WANG; LABUXIAGA; JIAYANGDUOJI; Yi XIE (Yixue yu zhexue)
During medical aid missions to Tibet, the cultural and religious differences between Han medical professionals and indigenous Tibetan patients have had a profound impact on the quality of medical services. Based on this, this study deeply analyzed the cultural characteristics and beliefs of indigenous Tibetan patients and examined the challenges and conflicts encountered by the Han medical-aid expert team in the diagnosis and treatment process, proposed the concept of cross-cultural tolerance in healthcare. Through the analysis of three typical clinical cases, this article explored how to maximize the protection of the health rights of Tibetan patients while respecting their culture and beliefs, promote harmonious coexistence between doctors and patients in terms of health and disease, beliefs and values, avoid cultural shock caused by cultural differences. Ultimately, it offered practical strategies to optimize the quality of medical services and provides insights and methods for healthcare support initiatives in ultra-high-altitude regions.